A138 ENDOSCOPIC SUBMUCOSAL DISSECTION FOR BARRETT'S NEOPLASIA IN A NORTH AMERICAN ACADEMIC CENTRE. (4th March 2021) - Motomura, D; Bechara, R
Abstract: Background: Endoscopic submucosal dissection (ESD) is carving out an increasing role in the treatment of Barrett's associated neoplastic lesions. Though endoscopic therapy is classically performed with endoscopic mucosal resection (EMR) and radiofrequency ablation (RFA), ESD provides the advantage of en-bloc resections, and greater R0 resection rates, which are defined as negative deep and lateral margins on histology. Aims: Our aim is to present procedural outcomes and subgroup analysis from one of the largest single centre cohorts of esophageal ESD in North America, and the first from Canada. Methods: All patients undergoing esophageal ESD for Barrett's neoplasia between Oct 2016 and June 2020 at a single tertiary care centre in Canada were included in the cohort. Demographic, procedural data and lesion characteristics are presented. Subgroup analysis was performed on patients who underwent extensive resection (≥75% of esophageal circumference) and patients who developed strictures. Statistical analysis included chi square testing on categorical variables and unpaired t-test for continuous variables. Binomial univariable logistic regression was performed to investigate factors associated with stricture formation. Results: Thirty-four patients underwent esophageal ESD for Barrett's associated neoplasia during the study period. The median lesion diameter was 5.7 cm (IQR 4.2 -7.5) and median procedure time 129 min (IQR 66–200). The en-bloc resection rate was 97%, and the R0 resection rate was 91%. Curative resection was achieved in 82% of patients. Upstaging from the pre-resection biopsy to post-ESD histology occurred in 59% of cases. Two adverse events occurred (1 delayed bleed, 1 aspiration event). There were no perforations. Procedural outcomes were similar between patients with extensive resections, but patients with ≥75% circumferential resection developed more strictures (65% vs 13%, p=0.001). Stricture formation was associated with extensive resection (OR 15.4, 95%CI[2.50 - 95.01]) and longer lesion diameter (OR 1.73, 95%CI [1.11 - 2.70]). Conclusions: Our experience with ESD for Barrett's related neoplasia shows excellent en-bloc and R0 resection rate, and provides more accurate histological specimens. Curative resection is possible in the vast majority of cases, including those with extensive resections. Further investigation into stricture prophylaxis will be useful as larger resections are attempted. Funding Agencies: None